ANALISIS SELF CONFIDENCE SISWA KELAS X HT 3 SMK SANGKURIANG 2 DALAM PEMBELAJARAN MATEMATIKA - Masruroh, Ani Ainun; Faturohman, Yusuf; Hidayat, Wahyu; Rohaeti, Euis Eti (IKIP Siliwangi, 2019)
SMA/SMK was the last high school before going to College. High school students/CMS are at the stages of adolescent age. The World Health Organization (1974) set the age limit of 10-20 years as a teenage limit (Sarwono,2008). Based on a review of the theory of progression, the age of adolescence is a time of onset of rapid changes, such as physical changes, changes in fundamental aspects of cognitive, emotion, social and achievement. Teens experiencing instability from time to time and they try to adopt new behavior from the previous development phases (Soetjiningsih,2004). Teens often have problems because of her unstable and still has not been formed in cooked. The attitude of the labile affected the level of confidence, such as the fearless try and there are times when his minder with her own.